Post-delivery mycobacterium tuberculosis infection misdiagnosed as systemic lupus erythematosus - Li Yu Ting; Bikash Shrestha; Yi Lu Lu; Fu Ping (Journal of Infection in Developing Countries)
Tuberculosis is a common infectious mycobacterial disease having a wide range of clinical and serological manifestations that are similar to rheumatic disease. Differential diagnosis is a crucial aspect in any rheumatic disease as many other infectious diseases portray clinical similarities and autoantibody positivity. Our case report illustrates of a young woman just after the delivery of a child presented an unusual case of extrapulmonary tuberculosis infection initially misdiagnosed as systemic lupus erythematosus (SLE).